2021
DOI: 10.3389/fmars.2021.690401
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Invasive Freshwater Mussels (Dreissena sp.): Spatiotemporal Variation and Occurrence With Chemical Contaminants

Abstract: Invasive zebra and quagga mussels (Dreissena spp.) in the Great Lakes of North America are biomonitors for chemical contaminants, but are also exposed to microplastics (<5 mm). Little research has examined in situ microplastic ingestion by dreissenid mussels, or the relationship between microplastics and chemical contaminants. We measured microplastics and chemical contaminants in mussel tissue from Milwaukee Harbor (Lake Michigan, United States) harvested from reference locations and sites influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Yet, Phuong et al ( 2018 ) found that larger bivalves contained more microplastic than smaller ones, whilst Doucet et al ( 2021 ) reported a negative correlation between body size of the freshwater mussel Margaritifera margaritifera L. and the number of ingested microfibers. Hoellein et al ( 2021 ) found that Dreissena polymorpha < 1 cm had significantly less microplastic per individual than organisms with a size between 1 and 2.5 cm, and when reported per gram wet weight, the size class with the highest concentration was the size class 1–1.5 mm whereas mussels < 1 cm and > 2.5 had the lowest concentration. This supports the chosen size of mussels for this study, as well as the fact that they are more numerous than larger individuals and thus are easier to sample—and they have a higher filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, Phuong et al ( 2018 ) found that larger bivalves contained more microplastic than smaller ones, whilst Doucet et al ( 2021 ) reported a negative correlation between body size of the freshwater mussel Margaritifera margaritifera L. and the number of ingested microfibers. Hoellein et al ( 2021 ) found that Dreissena polymorpha < 1 cm had significantly less microplastic per individual than organisms with a size between 1 and 2.5 cm, and when reported per gram wet weight, the size class with the highest concentration was the size class 1–1.5 mm whereas mussels < 1 cm and > 2.5 had the lowest concentration. This supports the chosen size of mussels for this study, as well as the fact that they are more numerous than larger individuals and thus are easier to sample—and they have a higher filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared particles for polymer identification as described in Barrows et al (2018) and Hoellein et al (2021). We wrapped glass microscope slides in aluminium foil and rinsed with filtered DI water.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of microplastic beads chosen to be injected into each mussel was informed by microplastic counts from quagga mussels collected from the St. Lawrence River, which ingested 2-11 microplastic particlesÁindividual À1 (Supplementary Table S2) and 2-4 beadsÁindividual À1 (Supplementary Table S3). Given that round gobies consume 30-40 dreissenid mussels daily (Naddafi and Rudstam 2014), they would be exposed to at least 18-24 microplastic particles daily from trophic transfer, assuming quagga mussel body burden is similar to that reported in the Great Lakes Basin (Hoellein et al 2021; Supplementary Tables S2, S3). To be conservative, we chose concentrations of 10 beadsÁmussel À1 as a low microplastic treatment.…”
Section: Experimental Designmentioning
confidence: 99%